2017
DOI: 10.18203/issn.2454-2156.intjscirep20170354
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of male wistar rats fed graded levels of stored powdered Corchorus olitorius

Abstract: <p class="abstract"><strong>Background:</strong> This study was carried out to determine the growth performance of rats fed graded levels of <em>Corchorus olitorius</em> supplemented diet.</p><p class="abstract"><strong>Methods:</strong> Twenty male wistar rats weighing between 70g and 90g were purchased and randomly allocated into four treatment groups with graded levels of <em>Corchorus</em> <em>olitorius</em> ( 2.5%, 5% and 10%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…To clarify which factor directly impacts the increase in body weight, a normal diet was used in this study. As mentioned above, compared with rats, mice have a higher feeding efficiency ratio and higher energy metabolic rate (23)(24)(25) . It has been suggested that mice respond more to dietary conditions and are suitable for dietary intervention studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify which factor directly impacts the increase in body weight, a normal diet was used in this study. As mentioned above, compared with rats, mice have a higher feeding efficiency ratio and higher energy metabolic rate (23)(24)(25) . It has been suggested that mice respond more to dietary conditions and are suitable for dietary intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the role of skipping breakfast on lipid metabolism, a normal diet was adopted in the present study. The feeding efficiency ratio of mice is known to be higher than that of rats (23,24) . Mice are also known to exhibit higher energy metabolic rates than rats (25) and to respond more to dietary conditions.…”
mentioning
confidence: 99%
“…The percent change in body weight was calculated according to ( Kunle et al, 2017 ) using the following formula: % Body weight change = Final body weight – initial body weight/initial body weight × 100 …”
Section: Methodsmentioning
confidence: 99%